2006
DOI: 10.1111/j.1538-7836.2005.01708.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of p38 MAPKinase/cPLA2 pathway in homocysteine‐treated platelets

Abstract: Hyperhomocysteinemia is considered a risk factor in arterial and venous thrombosis. The mechanism by which homocysteine (HCy) supports atherothrombosis is still unknown and may be multifactorial. Earlier in vitro studies demonstrated that HCy induced arachidonic acid release and increased thromboxane B2 (TXB2) formation. In this work, we found that HCy stimulated the rapid and sustained phosphorylation of platelet p38 mitogen-activated protein kinase (p38 MAPK). The effect was time- and dose-dependent. The HCy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
31
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 46 publications
6
31
0
1
Order By: Relevance
“…29,30 In platelets, phosphorylation of cPLA 2 has been documented to occur in response to several different agonists, including thrombin, and to be mainly mediated by p38 MAPK rather than ERK1/2. [31][32][33][34] In the present study, we confirmed that thrombin-induced phosphorylation of cPLA 2 in mouse platelets is prevented by the specific p38 MAPK inhibitor SB203580 (data not shown) and also documented that cPLA 2 phosphorylation is significantly reduced in platelets lacking Pyk2. In addition we found that in thrombin-stimulated platelets, the phosphorylation of p38 MAPK, but not ERK1/2, was reduced in the absence of Pyk2.…”
Section: Org Fromsupporting
confidence: 79%
See 1 more Smart Citation
“…29,30 In platelets, phosphorylation of cPLA 2 has been documented to occur in response to several different agonists, including thrombin, and to be mainly mediated by p38 MAPK rather than ERK1/2. [31][32][33][34] In the present study, we confirmed that thrombin-induced phosphorylation of cPLA 2 in mouse platelets is prevented by the specific p38 MAPK inhibitor SB203580 (data not shown) and also documented that cPLA 2 phosphorylation is significantly reduced in platelets lacking Pyk2. In addition we found that in thrombin-stimulated platelets, the phosphorylation of p38 MAPK, but not ERK1/2, was reduced in the absence of Pyk2.…”
Section: Org Fromsupporting
confidence: 79%
“…[29][30] In platelets, cPLA 2 phosphorylation is mainly mediated by p38 MAPK. [31][32][33][34] Figure 6A shows that thrombin-induced cPLA 2 phosphorylation on Ser505 was significantly reduced in Pyk2-deficient platelets compared with those from WT littermates. In agreement with previous findings, we confirmed that cPLA 2 phosphorylation in thrombin-stimulated platelets was mediated by p38 MAPK, because it was prevented by the specific inhibitor SB203580 (data not shown).…”
Section: Impaired Platelet Activation and Aggregation In The Absence mentioning
confidence: 99%
“…Hcys increases intracellular levels of Ca 2ϩ in platelets, dorsal root ganglion cells, motor neurons, and vascular smooth muscle cells (Mujumdar et al, 2000;Adalbert et al, 2002;Tjiattas et al, 2004;Leoncini et al, 2006). Hence, the effects of Hcys on cell-cell and cell-substrate interactions could be due to an effect of Hcys on intracellular Ca 2ϩ signaling.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies showed that MAPKs, including p38 MAPK (Leoncini et al, 2006), ERK (Su et al, 2004), and JNK (Casas et al, 2009), also induce cPLA 2 phosphorylation. However, our results indicate that phosphorylation of cPLA 2 was not observed after 2 h of stimulation with LPS (data not shown).…”
mentioning
confidence: 99%